Workplace Indirect Cost Impacts of Nasal and Sinus Symptoms and Related Conditions. Issue 8 (August 2019) - Kuiper, Jordan R.; Hirsch, Annemarie G.; Bandeen-Roche, Karen; Sundaresan, Agnes S.; Tan, Bruce K.; Kern, Robert C.; Schleimer, Robert P.; Schwartz, Brian S.
Abstract : Objective: Evaluate associations of nasal and sinus and related symptoms, as well as selected health conditions which produce those symptoms, with total lost productive time (LPT) at work in the past 2 weeks. Methods: We used a cross-sectional analysis of 2402 currently working subjects. Self-reported physician diagnoses, condition statuses measured with standardized instruments, and symptom-based factor scores from an exploratory factor analysis were used in survey weighted log-binomial regression. Results: Pain and pressure, nasal blockage and discharge, and asthma and constitutional symptom factor scores as well as self-reported allergic rhinitis were associated with higher total LPT. Individuals who met operationalized criteria for multiple health conditions, especially chronic rhinosinusitis, had the greatest total LPT. Conclusions: Better management of these symptoms, and awareness of how they impact an individual's ability to perform job-functions in the workplace, could improve overall productivity. Abstract : Supplemental Digital Content is available in the text